2021
DOI: 10.15294/eej.v11i1.47800
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Psychological Factors influencing the Students’ Anxiety in Speaking English

Abstract: Speaking is a productive skill that can be directly observed by considering several aspects. It can trigger the students’ anxiety as a psychological factor to communicate foreign language with others. This case has become a unique phenomenon to be analysed because anxiety has a relevance with foreign language abilities. This study aims to evaluate the psychological factor influencing the students’ anxiety in speaking English by using a qualitative approach. The data were collected by using observations, open-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…They also mentioned feeling nervous or embarrassed when speaking English, fearing that the students may make mistakes or be judge by others. In line with the study from Umisara, et al (2021), which focused on evaluating the influence of anxiety on students' English learning at SMP Brebes, it was found that the students' language learning experience was significantly affected by their anxiety levels. The research revealed that high levels of anxiety hindered their language proficiency development, making it more challenging for students to overcome their language difficulties.…”
Section: Finding and Discussionsupporting
confidence: 62%
“…They also mentioned feeling nervous or embarrassed when speaking English, fearing that the students may make mistakes or be judge by others. In line with the study from Umisara, et al (2021), which focused on evaluating the influence of anxiety on students' English learning at SMP Brebes, it was found that the students' language learning experience was significantly affected by their anxiety levels. The research revealed that high levels of anxiety hindered their language proficiency development, making it more challenging for students to overcome their language difficulties.…”
Section: Finding and Discussionsupporting
confidence: 62%
“…Those reasons ultimately led them to choose silence. According to Umisara et al (2021), pupils in the classroom struggle with speaking English, leading to shyness and lack of confidence. This example was also identified in the research conducted by Damayanti & Listyani (2020).…”
Section: Communication Apprehensionmentioning
confidence: 99%
“…Furthermore, certain students have received adverse assessments that have caused them trauma and instilled a fear of speaking English. Previously stated, they were fearful of receiving poor evaluations from professors or peers since it could diminish their enthusiasm to learn speaking (Umisara et al, 2021)…”
Section: Fear Of Negative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The students' anxiety makes them like to underestimate themselves, due to feeling afraid, frustrated, shy, worried, and nervous to do the interaction in English classes. These things are classified as psychological problems that provoke students' anxiety Umisara et al (2021). If anxiety occurs in the learning process at school, such as doing tests, school assignments.…”
Section: Introductionmentioning
confidence: 99%